Expanding the molecular spectrum of tenosynovial giant cell tumors - Gauduchon, Thibault; Vanacker, Helene; Pissaloux, Daniel; Cassier, Philippe; Dufresne, Armelle; Karanian, Marie; Meurgey, Alexandra; Bouhamama, Amine; Gouin, François; Ray-Coquard, Isabelle; Blay, Jean-Yves; Tirode, Franck; et al. (Frontiers in Oncology, 2022)
Background While great advances in clinical and pathological description of tenosynovial giant cell tumors (TGCT) have been made, TGCT molecular heterogeneity represents an ongoing challenge. The canonical oncogenic fusion CSF1::COL6A3 is not systematically observed, suggesting that other oncogenic mechanisms are involved in tumorigenesis. This study aims to explore by RNA sequencing a retrospective series of tumors diagnosed as TGCT, in order to provide a better description of their molecular landscape and to correlate molecular features with clinical data. Methods We analyzed clinicopathological data and performed whole-exome RNA sequencing on 41 TGCT samples. Results RNAseq analysis showed significant higher CSF1 and CSF1-R expression than a control panel of 2642 solid tumors. RNA sequencing revealed fusion transcripts in 14 patients including 6 not involving CSF1 and some previously unreported fusions. Unsupervised clustering on the expression profiles issued from this series suggested two distinct subgroups: one composed of various molecular subtypes including CSF1 and FN1 rearranged samples and one composed of four tumors harboring an HMGA2::NCOR2 fusion, suggesting distinct tumor entities. Overall, 15 patients received at least one systemic anti-CSF1R treatment and clinical improvement was observed in 11 patients, including patients from both clusters. Discussion This study reported molecular heterogeneity in TGCT, contrasting with the clinical and pathological homogeneity and the ubiquitous high CSF1 and CSF1R expression levels. Whether molecular diversity may impact the efficacy of systemic treatments needs to be further investigated.